2017
DOI: 10.1080/14494035.2017.1322772
|View full text |Cite
|
Sign up to set email alerts
|

Ruling out learning and change? Lessons from urban flood mitigation

Abstract: This article shows how particular rule configurations can create conditions for learning from experimentation on an operation level. It does so by using the IAD framework in a diagnostic analysis of decisions to fund the development of drainage in the Denver Metropolitan Area before and after the 2013 Colorado Flood. The discussion first synthesizes recent developments in this research area. Then, it demonstrates how formal institutional analysis can be used to address existing gaps. To conclude, recommendatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…In the social learning research, for example, 'the average number of training events a respondent attended per year during his tenure' was used by Arnold (2014) as a proxy for 'structured knowledge acquisition' in the context of wetland regulation. Similarly, changes in institutional designs and in rule configurations also indicated that learning occurred in policy change processes, as exemplified in a study focusing on urban flood mitigation in Colorado (Witting, 2017; see also Howlett et al, 2017;Panke, 2010, p. 810). In the research stream on policy interdependency, several successful policy adoptions across geographical entities were regularly used as proxies for policy learning (e.g., Kahn-Nisser, 2015;Shipan & Volden, 2014).…”
Section: Operationalization Of the Conceptmentioning
confidence: 93%
See 3 more Smart Citations
“…In the social learning research, for example, 'the average number of training events a respondent attended per year during his tenure' was used by Arnold (2014) as a proxy for 'structured knowledge acquisition' in the context of wetland regulation. Similarly, changes in institutional designs and in rule configurations also indicated that learning occurred in policy change processes, as exemplified in a study focusing on urban flood mitigation in Colorado (Witting, 2017; see also Howlett et al, 2017;Panke, 2010, p. 810). In the research stream on policy interdependency, several successful policy adoptions across geographical entities were regularly used as proxies for policy learning (e.g., Kahn-Nisser, 2015;Shipan & Volden, 2014).…”
Section: Operationalization Of the Conceptmentioning
confidence: 93%
“…Third, an increasing number of studies are adopting a direct approach to the operationalization of learning with a focus on the measurement of cognitive and mental updates. However, indirect approaches based on proxies for policy learning, such as changes in institutional designs (Witting, 2017), should not be overlooked as they are useful for examining whether policy learning leads to changes in actual policies and institutions (Moyson et al, 2017).…”
Section: Operationalization Of the Conceptmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the Basurto, Siddiki et al approach is amenable to the study of laws (leyes), regulations, and bylaws (reglamentos)-statutes (estatutos)-it is useful for the purposes of this paper. Furthermore, IGT has recently been applied to analyses of the recently reformed Nicaraguan water law [87], diagnosing decisions to fund the development of drainage in the Denver Metropolitan Area before and after the 2013 Colorado floods [88], and evaluating Ukrainian soil protection policy [89].…”
Section: Methodsmentioning
confidence: 99%